Engineered ferritin nanocage as a cholesterol sequestering agent - Ravishankar, Samyukta (Nanyang Technological University, 2021)
Accumulation of lipid laden macrophages (foam cells) is characteristic of atherosclerosis development in the arterial walls. Clinically, the current line of treatment includes using preventive drugs to maintain serum cholesterol levels and emergency surgical interventions at the onset of a heart attack. Therapeutic moieties such as peptides and small molecules directly targeting plaque cholesterol delivered using a transport vehicle has been recognized to potentially be a non-invasive tool for atherosclerosis management. In this thesis, the use of surface modified ferritin protein nanocages is proposed for the display of cholesterol sequestering agents for intracellular cholesterol reduction from atherosclerotic foam cell models. Ferritin cages have been modified by chemical and genetic methods to incorporate the therapeutic moieties. As a physical sequestration method, he use of hydrophobic cyclodextrin conjugated to ferritin nanocages as cholesterol sequestering agents is proposed. Cyclodextrin molecules are chemically conjugated to the ferritin nanocages surface or encapsulated within the nanocages using metal co-loading methods. The cyclodextrin conjugated ferritin has nanomolar affinity to cholesterol molecules as measured using biolayer interferometry. Treatment of foam cells with the conjugates shows decreased levels of intracellular accumulated cholesterol. Interaction of cyclodextrin with membrane cholesterol are observed to play a crucial role in cholesterol reduction with minimal cholesterol sequestration efficacy observed with cyclodextrins loaded within the inner cavity of ferritin. As an alternative mechanism of cholesterol sequestration, HDL mimetic peptides were genetically fused to the N-terminus of the cage for surface display. The secondary and quaternary ferritin structures are found to remain intact after peptide modification. Up to 30% reduction in intracellular cholesterol levels were achieved within 24h of treatment with the conjugates in a concentration dependent manner using the foam cell models. Efflux receptor analysis of treated samples demonstrates ABCA1 mediated cholesterol efflux mechanism using mimetic peptides as opposed to a physical sequestration using cyclodextrin molecules. To further understand the interaction mechanisms of ferritin with macrophages, in-depth internalization and molecular response studies are carried out. Ferritin is observed to be internalized by a transferrin receptor-mediated endocytosis pathway with cavolae and micropinocytosis concurrently playing a role in the uptake. Subcellular localization and transmission electron micrographs reveal endosomal localization with subsequent lysosome induced degradation of the protein shell and release of the iron core in the cytoplasm. mRNA upregulation of iron regulation relevant proteins and iron export is further measured with prolonged incubation. Lastly, preliminary pilot studies with atherosclerotic mice models reveal aortic localization of ferritin within 1h with greater than 95% of the macrophages in the lesion site homing the nanoparticles. This thesis thus includes the successful incorporation of therapeutic agents for cholesterol sequestration from an atherosclerotic marker, foam cells. Coupled with the internalization properties in macrophages and foam cells, this project emphasizes the potential of ferritin protein cages to be used as transport vehicles for cholesterol reduction in atherosclerosis management.